Medical student assessments—frequency of radiological images used: a national study - Chew, Cindy (BJR Open, 2020)
OBJECTIVES: Assessments are a key part of life for medical students at University. We know there is variation in these assessments across Universities. The aims of this study were to expatiate summative assessments in Scottish Medical Schools and to examine how frequently radiological images feature in them. METHODS: All Scottish medical schools were invited to participate in the study. Data on objective structured clinical examinations (OSCEs; 5 years) and written assessments (3 years) were retrospectively collected for each university and results were collated. Each University was randomly assigned a letter from A to E and anonymised for data presentation. RESULTS: 10,534 multiple choice questions (MCQ) and 1083 OSCE stations were included in this study. There was wide variation in the number, type and timing of assessments across Scottish medical schools. There were highly significant differences in the number of OSCE stations and the number of MCQs set over the study period (p < 0.0001). Radiological images were used on average 0.6 times (range 0–1.1) in each OSCE examination and 2.4 times (range 0.1–3.7) for written assessments. CONCLUSION: In this detailed study, we demonstrated significant differences in medical student assessments across Scottish Universities. Given the importance of Radiology in modern medicine, the frequency and differences in which radiological images were used in assessments across Universities should be addressed. ADVANCES IN KNOWLEDGE: This is the first national longitudinal study to quantify the role of radiological images in summative Medical Student Assessments. Great variability exists in the extent and how (clinical versus written assessments) radiological images are used to assess Scottish medical students. Radiological images are used infrequently in clinical assessments, but are present in every written assessment. These findings could help inform medical schools and academic radiologists as they prepare medical students for the imminent unified medical licensing examination, where Clinical Imaging is a subject with one of the highest number of associated conditions examinable.